2019
DOI: 10.4314/sajas.v49i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics, <i>Saccharomyces</i> spp.Kb-5 and Kb-8, in diets on growth performance and cholesterol levels in ducks

Abstract: The study was conducted to determine the effect of the probiotics, Saccharomyces spp.Kb-5 and Saccharomyces spp.Kb-8, on growth performance, carcass characteristics, serum and meat cholesterol levels in ducks. Two hundred and forty 1-day-old healthy male ducks were randomly allocated to four treatment groups: A) basal diet (control), B) basal diet + 0.20% Saccharomyces spp.Kb-5, C) basal diet + 0.20% Saccharomyces spp.Kb-8, and D) basal diet + 0.10% Saccharomyces spp.Kb-5 + 0.10% Saccharomyces spp.Kb-8. Growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 30 publications
0
8
0
8
Order By: Relevance
“…During the whole study period, the birds treated with B. subtilis and S. boulardii and enzyme showed comparatively better FCR than those supplementing with antibiotic ciprofloxacin. The live weight and FCR were higher in birds treated with B. subtilis and S. boulardii along with the enzyme than in other groups [ 23 , 24 ]. The growth performance of experimental birds was recorded higher in probiotic treatment than the birds that received the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…During the whole study period, the birds treated with B. subtilis and S. boulardii and enzyme showed comparatively better FCR than those supplementing with antibiotic ciprofloxacin. The live weight and FCR were higher in birds treated with B. subtilis and S. boulardii along with the enzyme than in other groups [ 23 , 24 ]. The growth performance of experimental birds was recorded higher in probiotic treatment than the birds that received the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested that dietary SC improved feed intake, daily gain, and FCR in broilers, and mitigated the negative effects of aflatoxin on broiler growth performance ( Afsharmanesh et al, 2010 ). Some scholars have also confirmed that SC could help improve production performance in meat duck study ( Bidura et al, 2019 ). In the present study, SC contributed to the FCR of Pekin ducks, which was consistent with previous studies on broilers ( Afsharmanesh et al, 2010 ; Pizzolitto et al, 2013 ).…”
Section: Discussionmentioning
confidence: 88%
“…SC was reported to be able to improve barrier function by preventing the LF82-induced expression of pore-forming claudin2 ( Sivignon et al, 2015 ), and it could relieve the decreased protein expression of ileum claudin induced by Escherichia coli in piglets ( Che et al, 2017 ). Besides, some findings also suggested that SC helped to improve the growth performance ( Bidura et al, 2019 ), immunity function antioxidant properties ( Nelson et al, 2020 ), and gut microbial community structure ( Wang et al, 2016 ) of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces spp. used in the TWC fermentation process can act as a probiotic in the digestive tract of hen, thereby increasing enzymatic activity and nutrient absorption (Zurmiati et al 2014;Liu et al 2015;Aristawati et al 2019;Bidura et al 2019b). Probiotic microbes can create a balance of intestinal microflora (Chang et al 2019;Khan et al 2022).…”
Section: Discussionmentioning
confidence: 99%